Evaluation of combinations of putative anti-biofilm agents and antibiotics to eradicate biofilms of Staphylococcus aureus and Pseudomonas aeruginosa - Belfield, Katherine; Bayston, Roger; Hajduk, Nadzieja; Levell, Georgia; Birchall, John P.; Daniel, Matija (Oxford University Press, 2017)
Objectives